Penggunaan project-based learning dan artificial intelligence dalam pembelajaran mahasiswa - Saragih, Sindy Febriany; Putra, Iwan; Kurniadi, Romi (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study aims to determine the use of project-based learning and artificial intelligence in student learning. The rapid development of technology in the digital era requires the world of education, especially higher education, to adopt innovative learning methods relevant to the needs of the 21st century. The study used a qualitative phenomenological approach through in-depth interviews with 8 informants consisting of lecturers and students of the Economics Education Study Program at the University of Jambi who were directly involved in project-based learning and the use of AI as an aid in completing academic assignments. The results showed that 100% of the integrated PjBL and AI activities were able to increase student activeness, creativity, collaboration, and contextual understanding according to 21st-century skills. However, its implementation still faces several challenges, both related to PjBL and the use of AI. To overcome these challenges, various solutions were implemented that support the creation of an adaptive, reflective, and contextual learning ecosystem. These findings imply the need for increased digital literacy and assistance in the use of AI. Further research can examine the effectiveness of PjBL and AI integration in other study programs or use a quantitative approach to obtain more measurable results.